Researches on the development of grading system and the determination of quality factors for fish - Nazif Anıl; Mustafa Nizamlıoğlu; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
This investigation was carried out to develop the grading system and to determine the quality factors for fish. On various sea fish the content of head, scales, fins, internal organs and fishbones ; the waste percentage ; the yield offish meat and the sensorial quality factors were determined. The waste percentages were found to be 28.04 % for anchovy, 35.93 %for horse mackerel, 29.64 %for bonito, 29.34 %for chub mackerel, 32.87 % for sea bream, 22.46 % for needlefish, 40.02 % for whiting. Hence, they have given 71.95 %, 64.04 %, 70.35 %, 70.65 %, 67.12 %, 77.53 % and 59.97 % meat yield, respectively. Furthermore, the sensorial acceptance levels for the same fish were valued at 8.31, 6.41, 9.04, 7.37, 6.47, 6.87, 7.88, respectively. Needlefish gave the highest meat yield (77. 53 %) due to its lowest waste percentage (22.46 %) but obtained an unsatisfactory result (6.87) from the organoleptic evaluation. On the other hand, whiting was not found valuable enought because of its highest waste percentage (40.02 %) and the lowest meat yield (59.97 %). It was proved that anchovy and bonito were the ideal fish for both their meat yield and as well as their sensorial acceptance level. As a result, the waste percentage, the meat yield and the organoleptic quality factors of various fish were determined, henceforth, a groundwork was laid down for the application of fish grading in our country in the future.